Jamestown Canyon virus detection in human tissue specimens. Issue 7 (19th January 2007) - Zheng, Huachuan; Murai, Yoshihiro; Hong, Mei; Nakanishi, Yuko; Nomoto, Kazuhiro; Masuda, Shinji; Tsuneyama, Koichi; Takano, Yasuo
Abstract : Aim: To clarify the advantages and disadvantages of different detection methods for Jamestown Canyon virus (JCV) in human tissue specimens. Methods: Specimens of lung and gastric carcinomas, and normal lung tissue, gastric mucosa, and tonsil were examined for T-antigen, VP and agnoprotein of JCV by nested PCR, Southern blotting and sequencing. JCV load targeting T-antigen was evaluated by real-time PCR, and JCV existence morphologically by immunohistochemistry, in-situ hybridisation (ISH) and PCR. For these experiments, the JCI cell line (JCV cultured neuroblastoma cell line) was employed as positive control. Results: In lung and gastric carcinomas, T-antigen, VP and agnoprotein of JCV could be detected by nested PCR whose products were confirmed by Southern blots and sequencing. With real-time PCR, frozen samples of gastric carcinomas gave better detection of JCV than their corresponding paraffin-embedded tissues (p<0.05). The positive rate of JCV was high in lung carcinoma, compared with normal lung tissue (p<0.05). It was the same for JCV copies in gastric carcinoma (p<0.05). Only the positive control exhibited JCV in the nucleus by ISH and immunohistochemistry. In-situ PCR showed that JCV genomic DNA was located in the nucleus of the carcinoma cell, some alveolar epithelial cells, and tonsil lymphocytes. In ISH and PCR, NBT/BCIP colouring was stronger than Fuchsin. Conclusions: Nested PCR whose amplicons should be confirmed by Southern blot and sequencing was a comparatively sensitive approach to detect JCV genomic DNA in human non-neural tissues. Real-time PCR might be employed to quantify copy number of JCV. In-situ PCR was a good method to observe the JCV location in cells, given appropriate modulation of amplification cycles. Combinations of various approaches will be adopted to explore the oncogenic roles of JCV in malignancies.